Phase I evaluation of the safety, tolerability, and pharmacokinetics of GSK3640254, a next‐generation HIV‐1 maturation inhibitor - Samit R. Joshi; Disala Fernando; Stephanie Igwe; Litza McKenzie; Anu S. Krishnatry; Fiona Halliday; Joyce Zhan; Thomas J. Greene; Jianfeng Xu; Geraldine Ferron‐Brady; Max Lataillade; Sherene Min (Wiley, 2020)
Abstract Despite advances in HIV‐1 management with antiretroviral therapy, drug resistance and toxicities with multidrug regimens can result in treatment failure. Hence, there is a continuing demand for antiretroviral agents (ARVs) with novel mechanisms of action. Maturation inhibitors inhibit HIV‐1 replication via a unique mechanism of action and can be combined with other ARVs. Two phase I randomized clinical trials were conducted for a maturation inhibitor, GSK3640254, to determine safety, pharmacokinetics (NCT03231943), and relative bioavailability (NCT03575962) in healthy adults. The first trial was conducted in two parts. Part 1 was conducted in a two‐cohort, interlocking, eight‐period fashion in 20 participants with single ascending doses of GSK3640254 (1‐700 mg) or placebo. In Part 2, 58 participants were randomized to receive GSK3640254 (n = 44) or placebo (n = 14). Four participants reported adverse events (AEs) leading to study discontinuation, with one adverse drug reaction (maculopapular rash). There was no relationship between frequency or severity of AEs and dose. Pharmacokinetic assessments showed that GSK3640254 was slowly absorbed, with time to maximum concentration (tmax) occurring between 3.5 and 4 hours and half‐life of ~24 hours. In the relative bioavailability study of GSK3640254 mesylate salt vs bis‐hydrochloride salt capsules in 14 healthy adults, the mesylate salt performed slightly better than the bis‐hydrochloride formulation (12%‐16% increase in area under the concentration‐time curve and maximum concentration); tmax (5 hours) was similar between the formulations. Initial pharmacokinetic and safety data from these healthy‐participant studies informed further development of GSK3640254 for once‐daily dosing for the treatment of HIV‐1 infection.